2016
DOI: 10.1097/aap.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Are Cure Rates for Breast Cancer Improved by Local and Regional Anesthesia?

Abstract: Breast cancer OS, DFS, and LRR were not affected by type of anesthesia in our institution. This result differs from that of the only prior published clinical report on this topic and does not provide clinical corroboration of the basic science studies that suggest oncologic benefits to LRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…Starnes-Ott et al 14 found that the recurrence rate in the volatile GA-opioid group was 1.4 per 100 000 person-days and 2.6 per 100 000 person-days in the PVB-GA group. In agreement with that study, Tsigonis et al 16 concluded that the OS, DFS, and local regional recurrence were not significantly different between women who received GA or local regional anesthesia. Lastly, Cata et al 17 showed similar RFS and OS estimates in women with and without PVB, despite demonstrating a significant reduction in the use of opioids on the PVB group.…”
Section: Discussionsupporting
confidence: 82%
“…Starnes-Ott et al 14 found that the recurrence rate in the volatile GA-opioid group was 1.4 per 100 000 person-days and 2.6 per 100 000 person-days in the PVB-GA group. In agreement with that study, Tsigonis et al 16 concluded that the OS, DFS, and local regional recurrence were not significantly different between women who received GA or local regional anesthesia. Lastly, Cata et al 17 showed similar RFS and OS estimates in women with and without PVB, despite demonstrating a significant reduction in the use of opioids on the PVB group.…”
Section: Discussionsupporting
confidence: 82%
“…Mean age of the patients was 54.1 ±2.41 (36-75). Excisional biopsy took 12.1±2.78 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) minutes and sentinel lymph node biopsy took 15.5±3.73 (10-23) minutes after local anesthesia was applied. Average time between excisional biopsy and sentinel lymph node biopsy was 27.1±3 days.…”
Section: Resultsmentioning
confidence: 99%
“…Anesthetic‐induced immunosuppression may differ between GA and local anesthesia/anesthetic sedation, and local anesthesia may reduce cancer recurrence and cancer‐related mortality. This difference may explain why previous retrospective studies on anesthetic techniques and cancer outcomes showed conflicting results in patients with breast cancer . Clinical trials are ongoing to compare different anesthetics in patients undergoing breast cancer surgery (NCT00418457; NCT02089178).…”
Section: Discussionmentioning
confidence: 99%